THE EFFECT OF LAVENDER AROMATHERAPY ON LABOR PAIN IN PRIMIPARA IN ACTIVE PHASE I - Sri Untari; Nurul Kodiyah; Nurya Kumalasari (Lppm Unan, 2022)
uterus, increasing anxiety, tension, fear and stress in facing labor which results in delays in the progress of labor. Labor pain can be treated using complementary therapy with aromatherapy techniques. Lavender aromatherapy can affect the limbic system in the brain which is the center of emotion, and is able to produce endorphins and enkephalins which have pain relieving properties and serotonin which has the effect of eliminating anxiety and tension. Lavender aromatherapy hasanticonvulsant, antidepressant, anxiolytic, and soothing properties during labor. Methods: The design of this study was a quasy experiment with a one group Pre-Post Test approach. The independent variable is giving Lavender aromatherapy. The dependent variable is labor pain. The population in this study was primiparous mothers, during April - June 2022, a sample of 28 respondents. Taking the side Non-probability sampling technique with purposive sampling. Data collection tool using Visual Analog Scale (VAS). Bivariate analysis using the Paired Sample T Test. The purpose of this study was to determine the effect of lavender aromatherapy on labor pain in primipara in the active phase of the first stage. Results: There was a decrease in the pain score before being given lavender aromatherapy with a value of 7.535 (severe controlled pain) and after being given lavender aromatherapy a value of 5.321 (moderate pain). Giving lavender aromatherapy to labor pain can effectively reduce labor pain. Conclusion: Thus it was concluded that there was an effect of giving lavender aromatherapy to the scale of labor pain in primipara in the active phase of the first stage.